Size Effect of Fe3O4 Nanoparticles on Magnetism and Dispersion Stability of Magnetic Nanofluid - Chen, Fang; Ilyas, Nasir; Liu, Xiaobing; Li, Zhenggui; Yan, Shengnan; Fu, Hao (Frontiers in Energy Research, 2021)
It is well known that magnetic nanofluids are widely applied in various fields ranging from heat transfer to miniature cooling, and from damping to sealing. Herein, we prepared Fe3O4 nanoparticles and PFPE-oil based magnetic nanofluids with improved magnetization and dispersion stability. The structures of particles were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The size effects of particles on the magnetism and coating effect of particles, and on the stability and saturation magnetization of the fluids were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), vibrating sample magnetometer (VSM) and density instrument, respectively. The results indicate that the impurity phase FeOOH only appear in the sample prepared at 18 oC and the average size of Fe3O4 reduces from 120 nm to 20 nm with raising reaction temperature. The saturation magnetization of Fe3O4 particles increases firstly and then reduces with increasing particle size, which is both affected by the thickness of magnetic dead layer and impurity phase FeOOH. The Fe3O4 particles could be chemically coated by PFPE-acids, and which is a little affected by particle size. The stability of the nanofluids lowers with increasing particle size, while the saturation magnetization of which increases firstly and then decrease. At reaction temperature of 60 oC, Fe3O4 particles of 25 nm and the magnetic nanofluids with high stability and high saturation magnetization were obtained. Our results indicate that the nanoparticles size regulation can be a useful strategy for preparing magnetic nanofluids with desirable properties for various potential applications.